From vicious to virtuous circles? Gender and micro-enterprise development - Linda Mayoux (United Nations Research Institute for Social Development (UNRISD), 1995)
In this paper the author reviews some of the past and current experience of micro-enterprise programmes for women: training, credit and producer groups and co-operatives. Although there are some successes, the evidence indicates that the majority of programmes fail to make any significant impact on women's incomes. Most programmes, including co-operatives, have on the whole benefited better-off women. They cannot be assumed to have a beneficial impact on gender inequalities, but may increase workloads without increasing access to incomes within the household. They also cannot be assumed to be of greater benefit than other types of employment programmes to women labourers. The author argues that the diversity of the small-scale sector on the one hand, and the complexity of constraints posed by poverty and inequality on the other, make the likelihood of any easy "blueprint" for successful women's micro-enterprise development extremely slim. Both the market and empowerment approaches to micro-enterprise development contain a number of inherent tensions. These are complicated rather than resolved through the co-option of participation within the market approach, and greater attention to efficiency within the empowerment approach. What is clear from this paper is that micro-enterprise development for women is unlikely to be an "all-win", "bottom-up" solution to a wide range of development problems, as much of the rhetoric would imply. It cannot be seen as a substitute for welfare programmes or direct efforts to support labour and address gender inequality. Even in terms of narrow aims of increasing beneficiary incomes, micro-enterprise development is unlikely to succeed for the vast majority of poor women (rather than a small number of better-off women) unless it is part of a transformed wider agenda. There are particularly serious implications for any reliance on micro-enterprise programmes as the main focus of a wider strategy for poverty alleviation and change in gender inequality.
Keywords: 330